Variation of the specific gravity and fiber length of Juniperus phoenicea L. tree grown in AL-Jabal AL- Akhdar Region - Faraj, Hameda A. y.; Mahmood, Anees M. (Al-Mukhtar Journal of Sciences, 2021)
This study aimed to investigate the effect of geographical location, direction, and age on wood specific gravity and fibre length of the Phoenician juniper (Juniperus phoenicea L.) tree in the Al-Jabal Al-Akhdar region. Nine sites over three terraces were selected. The study was carried out on growth rings at d.b.h. for one tree of each site. The results revealed a decrease in wood specific gravity values with the increase in the distance from the pith, which ranged from 0.67 to 0.83. There were also significant differences in wood specific gravity values between the three terraces. The fibre length values ranged from 2.136 to 2.460 mm. A positive correlation between the fibre length and the distance from the pith with age was found, which increased with the increase in the distance from the pith. The study also showed significant differences in the values of mean fibre length between the different terraces, where the highest values were in the third terrace. On the same pattern, the direction influenced significantly the values of mean fibre length, where the trees in the centre have higher values of fibre length than those in the other two directions. The wood specific gravity values were significantly high in the trees grown under environmental stress in the first terrace near to the sea level, where the trees have a low tree growth rate. While the values of mean fibre length were high on the third terrace, confirming the increase in the tree growth rate and size.